Metal-on-metal total hip arthroplasty - five- to 11-year follow-up. - Nikolaou, Vassilios S; Petit, Alain; Debiparshad, Kevin; Huk, Olga L; Zukor, David J; Antoniou, John (Bull NYU Hosp Jt Dis, 2011)
Metal-on-metal (MoM) total hip arthroplasty (THA) has been introduced in an attempt to reduce the wear rate and the consequent osteolysis around implants. The aim of this study was to present the intermediate to long-term clinical and radiological outcomes and to investigate the metal ion levels in the blood of patients who had undergone primary uncemented MoM THA in our institution. Between July 1997 and November 2003, 166 patients (193 hips), with a mean age of 50 years (range, 18-65 years), underwent primary MoM THA. Clinical data, radiographs, and blood samples were obtained at regular follow-up visits. Cobalt (Co), chromium (Cr), and molybdenum (Mo) ions were measured by inductively coupled plasma-mass spectrometry (ICP-MS) from the patient's whole blood. All patients were prospectively followed for a minimum of 5 years (mean, 7 years; range, 5-11 years). The mean Harris hip score (HHS) and the University of California at Los Angeles (UCLA) activity score at the latest follow-up was 88 ± 11 and 7 ± 1.8 points, respectively. Thirteen hips have been revised. Ten acetabular components had early failure, due to factory manufacturing problems. All other implants have been found stable, with no signs of aseptic loosening. The probability of survival at 11 years, if the hips that were revised due to manufacturing problems were excluded, was 98.4%. The Co and Cr metal ion levels, after increasing significantly during the first 4 to 5 years post-surgery, remained stable, with a tendency to decrease thereafter, but not significantly. During the same follow-up period, Mo ion levels remained stable. In this 5-to-11 year follow-up study of MoM THA patients, excellent survivorship, with low complications rates, was found. Results of longer follow-up studies are necessary to clarify the possible long-term effects of metal ion release.
Keywords: Adult; Aged; Arthroplasty, Replacement, Hip; Chromium; Cobalt; Female; Follow-Up Studies; Hip Joint; Hip Prosthesis; Humans; Male; Middle Aged; Molybdenum; Prosthesis Failure; Radiography; Reoperation; Young Adult